Regulation of dndB Gene Expression in Streptomyces lividans - Dai, Daofeng; Pu, Tianning; Liang, Jingdan; Wang, Zhijun; Tang, Aifa (Frontiers in Microbiology, 2018)
DNA sulfur modification is a unique modification occurring in the sugar-phosphate backbone of DNA, with a nonbridging oxygen atom substituted with sulfur in a sequence-specific and Rp stereo-specific manner. Bioinformatics, RNA-seq, and in vitro transcriptional analyses have shown that DNA sulfur modification may be involved in epigenetic regulation. However, the in vivo evidence supporting this assertion is not convincing. Here, we aimed to characterize two sulfur-modified sites near the dndB promoter region in Streptomyces lividans. Single mutation of either site had no effect on dndB transcription, whereas double mutation of both sites significantly elevated dndB expression. These findings suggested that DNA sulfur modification affected gene expression, and the role of DNA sulfur modification in epigenetic regulation depended on the number of sulfur-modified sites. We also identified an inverted repeat, the R repeat sequence, and showed that this sequence participated in the positive regulation of dndB gene expression.